1983
DOI: 10.1016/s0022-5347(17)51106-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prazosin in Patients with Benign Prostatic Obstruction

Abstract: Prazosin, a selective alpha-1-adrenoceptor blocker, was used in a double-blind crossover study in 20 men with benign prostatic obstruction. Maximum and average flow rates increased, and residual volume and obstructive symptoms were reduced. Voiding pressure parameters, bladder capacity and irritative symptoms did not change significantly. No side effects were noted. We conclude that prazosin seems to be an effective therapeutic alternative in patients with benign prostatic obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0
4

Year Published

1988
1988
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(74 citation statements)
references
References 19 publications
5
65
0
4
Order By: Relevance
“…Based on in vitro findings, clinical trials of x-adrenoceptor blockers have been conducted to determine the effectiveness of phenoxybenzamine (Caine & Perlberg, 1977;Caine et al, 1978;Boreham et al, 1977;Abrams et al, 1982;Brooks et al, 1983) and prazosin Hedlund et al, 1983;Takita et al, 1983) in the medical treatment of benign prostatic hypertrophy.…”
Section: Methodsmentioning
confidence: 99%
“…Based on in vitro findings, clinical trials of x-adrenoceptor blockers have been conducted to determine the effectiveness of phenoxybenzamine (Caine & Perlberg, 1977;Caine et al, 1978;Boreham et al, 1977;Abrams et al, 1982;Brooks et al, 1983) and prazosin Hedlund et al, 1983;Takita et al, 1983) in the medical treatment of benign prostatic hypertrophy.…”
Section: Methodsmentioning
confidence: 99%
“…Following earlier studies with the alkylating agent phenoxybenzamine (Caine et al, 1978), competitive a 1 -adrenoceptor antagonists such as terazosin (Lepor, 1995), prazosin (Hedlund et al, 1983;Chapple et al, 1992) and alfuzosin (Buzelin et al, 1993) have been shown to be e ective in relieving urinary out¯ow obstruction and reducing symptom scores in patients with benign prostatic hyperplasia (BPH). However, the usefulness of a 1 -adrenoceptor antagonists in BPH is o set by their dose-limiting cardiovascular e ects, including postural hypotension, particularly with initial dosing.…”
Section: Introductionmentioning
confidence: 99%
“…The present study confirmed the stereochemical specificity of the optical isomers of LY253352 in human prostatic adenomas using competitive binding assays. (Caine et al, 1978;Hedlund et al, 1983). The in vitro contractile properties of prostatic tissues are mediated by a-adrenoceptors (Honda et al, 1985).…”
Section: Methodsmentioning
confidence: 99%